PROCEDURAL RHETORIC METHOD FOR TRANSMEDIA STORYTELLING ANALYSIS / МЕТОД ПРОЦЕДУРНОЙ РИТОРИКИ ДЛЯ АНАЛИЗА ТРАНСМЕДИЙНЫХ ПРОИЗВЕДЕНИЙ - MILOVIDOV STANISLAV V. / МИЛОВИДОВ С.В. (Наука телевидения)
The article analyzes the methodology of procedural rhetoric (I. Bogost) as applied to transmedia storytelling, making it possible to detect its specific network characteristics. With the development of digital technologies, the perception of transmedia works changes from narrative reception to interaction with the space. In this regard, a problem emerges associated with perception and analysis of such practices possessing spatial characteristics, since the traditional (i.e. linguistic) approach appears to have limited applicability and does not allow to research these objects in their entirety. To research this space constructed in users’ practices within the framework of procedural rhetoric, it is proposed to analyze individual operations (actions of a transmedia project participant) and map the resulting operational chains. Therefore, a vast array of data is created, combining all elements of a transmedia work into a single space, regardless of media format or media platform they are presented in. As a result, the role of non-human actors (fictional characters, interactive artifacts or computergenerated objects) turns out to be just as crucial as the role of users who get new information about the fictional world by partially creating it themselves. The space of a transmedia project may be presented, on the one hand, as an interface of interaction between its various parts and on the other hand, as an «actor-network» (B. Latour), where users’ communication is actualized as the dichotomy of embedding the fictional world into the real one and vice versa is gradually erased. Fictional worlds also reveal fractal properties, which gives reason to assume their fundamental incompleteness, and the scope of user’s participation becomes much broader than the author’s concept (canon). The reception and interaction of users with the project’s universe is of particular interest, since the path of each user is unique and the phenomenology makes it possible to analyze how the structural components of the fictional world (the sequence of exploring them or excluding some parts) affect the perception of transmedia storytelling and the trajectory of studying it.